2013
DOI: 10.1242/dev.080473
|View full text |Cite
|
Sign up to set email alerts
|

Distinct requirements for wnt9a and irf6 in extension and integration mechanisms during zebrafish palate morphogenesis

Abstract: SUMMARYDevelopment of the palate in vertebrates involves cranial neural crest migration, convergence of facial prominences and extension of the cartilaginous framework. Dysregulation of palatogenesis results in orofacial clefts, which represent the most common structural birth defects. Detailed analysis of zebrafish palatogenesis revealed distinct mechanisms of palatal morphogenesis: extension, proliferation and integration. We show that wnt9a is required for palatal extension, wherein the chondrocytes form a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 40 publications
(51 reference statements)
3
124
0
2
Order By: Relevance
“…For example, mammalian and fish palates have distinct morphologies and are comprised of non-homologous elements (Dougherty, et al 2013; Murray and Schutte 2004; Swartz, et al 2011). Despite this, their development requires the action of homologous cell- and tissue-level processes including migration of cranial neural crest cells, as well as the coordinated outgrowth and fusion of multiple processes and structures (Dougherty, et al 2013; Murray and Schutte 2004). Further, homologous genes regulate these cellular mechanisms.…”
Section: Harnessing Natural Variation In Evolutionary Mutants To Undementioning
confidence: 99%
See 1 more Smart Citation
“…For example, mammalian and fish palates have distinct morphologies and are comprised of non-homologous elements (Dougherty, et al 2013; Murray and Schutte 2004; Swartz, et al 2011). Despite this, their development requires the action of homologous cell- and tissue-level processes including migration of cranial neural crest cells, as well as the coordinated outgrowth and fusion of multiple processes and structures (Dougherty, et al 2013; Murray and Schutte 2004). Further, homologous genes regulate these cellular mechanisms.…”
Section: Harnessing Natural Variation In Evolutionary Mutants To Undementioning
confidence: 99%
“…Further, homologous genes regulate these cellular mechanisms. For instance, loss of irf6 or the microRNA Mirn140 and Pdgf signaling network results in conspicuous orofacial clefting in both humans and zebrafish (Dougherty, et al 2013; Eberhart, et al 2008; Kondo, et al 2002; Li, et al 2010; Rattanasopha, et al 2012). These insights confirm the deep homology of the vertebrate skull.…”
Section: Harnessing Natural Variation In Evolutionary Mutants To Undementioning
confidence: 99%
“…Comparable phenotypes have been observed in zebrafish “midline” mutants, ranging from a complete absence of the anterior neurocranium to the formation of two unfused, parallel rods or a single rod instead of a plate (Eberhart et al, 2008; Eberhart, Swartz, Crump, & Kimmel, 2006; Kimmel, Miller, & Moens, 2001; Swartz, Sheehan-Rooney, Dixon, & Eberhart, 2011; Wada et al, 2005). Importantly, zebrafish mutant for Pdgf, Shh, or Bmp pathway components, or deficient in irf6 , all show cleft or midline phenotypes resembling those of their mammalian counterparts (Table 1; Dougherty et al, 2013; Eberhart et al, 2008, 2006; Swartz et al, 2011; Wada et al, 2005). These findings indicate that a conserved genetic network regulates the formation of this part of the face across vertebrates and support the use of the zebrafish anterior neurocranium as a model for the mammalian hard palate.…”
Section: Zebrafish Craniofacial Anatomymentioning
confidence: 99%
“…Within the first stream of neural crest, the initial, premigratory rostral–caudal position alongside the brain determines whether NCCs will migrate over or behind the eye (Dougherty et al, 2012; Wada et al, 2005), as well as whether their progeny will contribute to the anterior neurocranium or the upper or lower jaw (Dougherty et al, 2013, 2012; Eberhart et al, 2006; Wada et al, 2005). Additional analyses demonstrated that NCCs at certain anterior–posterior and mediolateral coordinates within each arch reproducibly contribute not only to particular skeletal elements but also to specific domains of said elements (Fig.…”
Section: Imaging Craniofacial Developmentmentioning
confidence: 99%
“…4C–D) were observed. Further, we noted that the ethmoid cartilage, thought to be analogous to the mammalian palate in non-amniotes [69], was significantly reduced or absent. These defects were accompanied by a reduced midface area that was at least in part due to a decrease in cell proliferation in the dorsal facial prominences.…”
Section: Introductionmentioning
confidence: 99%